Hambatan Wirausaha pada Lulusan Perguruan Tinggi - Ni Putu Nurwita Pratami Wijaya; Fitriani Reyta (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
Unemployment is now a very complex problem in several developing countries. Some governments in developing countries have a number of programs to reduce this problem. One of them is Indonesia. The only solution to this problem is to increase the number of entrepreneurs, so that new jobs can be formed. In order to achieve this goal, a synergy between government and universities is needed to produce graduates who have entrepreneurial spirit. The purpose of this study is to look for factors that inhibit a person from entrepreneurship for college graduates. This research was conducted at Widyatama University, Bandung, Indonesia. By distributing a questionnaire of 100 questionnaires to respondents whose respondents were graduates of Widyatama University. This research was analyze with PLS (Partial Least Square) method and processed with XLSTAT software. The results showed that the most dominant factor being an obstacle in entrepreneurial intention was aversion to stress and hardwork with a value of 0.2333. Keywords: Entrepreneurial barriers, entrepreneur intention, graduates student.